2009
DOI: 10.29333/ejgm/82645
|View full text |Cite
|
Sign up to set email alerts
|

Role of Peroxisome Proliferator-Activated Receptor gamma 2 (PPAR-γ2) Gene Polymorphism in Type 2 Diabetes Mellitus

Abstract: Objective: To find out the relation between Pro 12 Ala polymorphism of peroxisome proliferator-activated receptor gamma2 (PPAR-g2) gene with type 2 diabetes mellitus and the possible role of this gene polymorphism as a link between obesity and type 2 diabetes mellitus. Subjects and Methods: Subjects of this study were classified into 3 groups: (15) Apparently healthy lean individuals (Group I), (15) obese non diabetic individuals (group II) and (24) patients with type 2 diabetes mellitus (group III). This grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
(19 reference statements)
1
5
0
2
Order By: Relevance
“…The results of the previous Egyptian study supported an association between Pro allele of PPARγ2 gene and T2D [28]. It is noteworthy that the unexplained high frequencies of the Ala allele observed among the Egyptian control subjects, in the previous study (53%) [28] and also in the current work (~39%), exceed any frequency reported.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results of the previous Egyptian study supported an association between Pro allele of PPARγ2 gene and T2D [28]. It is noteworthy that the unexplained high frequencies of the Ala allele observed among the Egyptian control subjects, in the previous study (53%) [28] and also in the current work (~39%), exceed any frequency reported.…”
Section: Discussionsupporting
confidence: 80%
“…The C1431T polymorphism has also been studied in relation to obesity, diabetes and coronary heart disease [18,[25][26][27]. After a meticulous review of the literature, we were able to find a single association study conducted on Egyptian individuals to explore the relation between Pro12Ala PPARγ2 variant and T2D risk [28]. However, to our knowledge, no association studies, evaluating the role of the C1431T variant in T2D, or investigating the associations of PPARγ2 variants with DR, have been published.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Activation of PPARγ2 results in an increase in the sensitivity of both the liver to insulin-mediated suppression of hepatic glucose production and insulin-mediated skeletal muscle glucose uptake. [26] PPARα and PPARγ have been reported to upregulate nitric oxide synthase and stimulate NO release, which is beneficial to counteract endothelial dysfunction commonly present in patients with metabolic syndrome, especially obesity, insulin resistance, and type 2 diabetes. [27]…”
Section: Role Of Pparγ Agonistmentioning
confidence: 99%
“…Сходные данные получены при обследо-вании лиц, проживающих в Египте [62]. Современные методы полногеномного ис-следования -Genome-Wide Association Studies (GWAS) -позволяют выявить ассоциации за-болеваний с сотнями тысяч полиморфных вари-антов генов.…”
Section: остеоартрит при диабетеunclassified
“…Показано, что среди жителей Китая у но-сителей полиморфизма rs12629751 гена PPARγ риск возникновения ОА коленных суста-вов увеличивается на 34% [75], а у французов и египтян аллель Pro12Ala РPARγ ассоциирован с риском развития СД 2 типа и инсулинорези-стентности [43,62].…”
Section: остеоартрит при диабетеunclassified